A comparative study of short-term outcomes of colorectal cancer surgery in the elderly population. Issue 5 (3rd September 2017) - Yen, Clarence; Simillis, Constantinos; Choudhry, Mariam; Mills, Sarah; Warren, Oliver; Tekkis, Paris P.; Kontovounisios, Christos
Abstract: Background: Colorectal Cancer (CRC) is a disease of the elderly, and with an ageing population, oncological surgical procedures for CRC in the elderly is expected to increase. However, the balance between surgical benefits and risks associated with age and comorbidities in elderly patients is obscure. Materials and methods: A retrospective database of consecutive patients who received CRC surgery was used to compare short-term surgical and oncological outcomes between patients aged ≥75 and <75 years old undergoing CRC resection. Results: There were 54 patients (63.5%) in the <75 group and 31 patients (36.5%) in the ≥75 group. Overall, there were no differences between the <75 and ≥75 groups in postoperative HDU/ITU stay, median hospital LOS or 30-day mortality rates. Patients ≥75 had a higher preoperative performance status (25.9% versus 71.0%, p < .001), but no difference in ASA Grade and referral pattern, proportion of emergency operations, cancer staging, resection margins, achievement of curative resection or median lymph node yield. There was a significantly higher use of adjuvant chemotherapy in the <75 age group (48.1% versus 25.8%, p = .043). Conclusions: With adequate patient selection, CRC resection in elderly patients is not associated with higher postoperative mortality or worse short-term oncological benefits.